1988
DOI: 10.1523/jneurosci.08-01-00079.1988
|View full text |Cite
|
Sign up to set email alerts
|

Selective staining of a subset of GABAergic neurons in cat visual cortex by monoclonal antibody VC1.1

Abstract: VC1.1 is a monoclonal antibody generated against cat area 17, which selectively outlines subsets of cortical neurons (Arimatsu et al., 1987). This study was conducted to determine the ultrastructural distribution of the VC1.1 antigen and to identify the particular subclasses of cortical neurons that were labeled. In the light microscope, VC1.1 delineated the surfaces of neurons located mainly in layer IV but also in other layers. The staining surrounded neuronal cell bodies and dendrites in a periodic or meshw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 28 publications
(45 reference statements)
3
31
0
Order By: Relevance
“…Deeply anesthetized Long Evans rats were perfused with 0.1 M sodium phosphate buffer, pH 7.4, containing 0.1 U/ml sodium heparin, followed by perfusion with ϳ250 ml of a fixative containing 4% paraformaldehyde and 0.2% glutaraldehyde in 0.1 M phosphate buffer, pH 7.4. The brains were left in the skull for 2 hr at 4ЊC, removed, blocked, and post-fixed in the perfusion solution for 4 hr (Naegele et al, 1988). Vibratome sections (100 m thick) were cut in coronal plane and collected in cold 0.1 M phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Deeply anesthetized Long Evans rats were perfused with 0.1 M sodium phosphate buffer, pH 7.4, containing 0.1 U/ml sodium heparin, followed by perfusion with ϳ250 ml of a fixative containing 4% paraformaldehyde and 0.2% glutaraldehyde in 0.1 M phosphate buffer, pH 7.4. The brains were left in the skull for 2 hr at 4ЊC, removed, blocked, and post-fixed in the perfusion solution for 4 hr (Naegele et al, 1988). Vibratome sections (100 m thick) were cut in coronal plane and collected in cold 0.1 M phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The contribution of Glc A3-S04 in cortical cells, for example, is known little beyond implications from comparative data showing their content of the calcium-binding protein parvalbumen (Kosaka et al, 1990) and of glutamic acid decarboxylase indicative of neuroinhibition (Naegele et al, 1988;Naegele and Barnstable, 1989). Localizing a substance of unknown significance at a site of specialized physiological activity allows for speculation concerning the constituent's functional contribution.…”
Section: Imentioning
confidence: 99%
“…Previous studies had demonstrated that GABAergic neurons with either bitufted or multipolar dendrites were stained preferentially by monoclonal antibodies VC 1.1 and VC5.1 or the lectin VVA (Naegele et al, 1988;Mulligan et al, 1989). These findings suggested that each marker identified more than one fundamental cell type.…”
mentioning
confidence: 97%
“…There is now evidence that certain plant lectins and monoclonal antibodies identify subsets of cortical local circuit neurons. Lectins from Viciu villosa (VVA) label N-acetylgalactosamine (GalNac)-containing molecules which are selectively enriched on the surfaces of many GABAergic neurons (Naka-gawaet al, 1986a, b;Naegeleet al, 1987;Mulliganet al, 1989 (Arimatsu et al, 1987;Naegele et al, 1988). Monoclonal antibody Cat-301 labels a large proteoglycan restricted to cell bodies and dendrites of approximately 80% of the GABAergic neurons in cat area 17, as well as some pyramidal neurons (Hockfield and McKay, 1983;Hendry et al, 1988;Zaremba et al, 1989a).…”
mentioning
confidence: 99%